The magnetosphere-ionosphere observatory (MIO) mission concept - Borovsky, Joseph E.; Bauer, Brian A.; Holloway, Michael (Frontiers in Astronomy and Space Sciences, 2022)
MIO (Magnetosphere-Ionosphere Observatory) is designed to definitively fix a cause-and-effect problem: In the nightside magnetosphere-ionosphere system we don’t know what is connected to what. The MIO mission concept is to operate a powerful 1-MeV electron accelerator on a main spacecraft in the equatorial nightside magnetosphere: the electron beam is directed into the atmospheric loss cone to deposit ionizing electrons in the atmosphere sufficient to optically illuminate the magnetic footpoint of the spacecraft while 4 nearby daughter spacecraft make equatorial magnetospheric measurements. A network of ground-based optical imagers across Alaska and Canada will locate the optical beamspot thereby unambiguously establishing the magnetic connection between equatorial magnetospheric measurements and ionospheric phenomena. Critical gradient measurements will be made to discern magnetospheric field-aligned-current generator mechanisms. This enables the magnetospheric drivers of various aurora, ionospheric phenomena, and field-aligned currents to be determined. In support of the Solar and Space Physics (Heliophysics) 2022 Decadal Survey, an experienced team of engineers and scientists at The Johns Hopkins University Applied Physics Laboratory (APL) have developed a NASA HMCS (Heliospheric Mission Concept Study) mission concept that can achieve the science objectives. The mission concept presented here is the result of trade studies that optimized the mission with regard to factors such as science objectives, concept study requirements, space environment, engineering constraints, and risk. This Methods paper presents an overview of the MIO concept.